Liquid crystal compound anti-ice surface. Issue 2 (26th January 2016) - Wang, Zeqing; Cong, Yuehua; Zhang, Baoyan
ABSTRACT: In some cold areas/regions, ice accumulation is harmful to aircrafts, highways and power lines. To overcome this challenge, many researchers have focused on developing anti-icing surfaces. In this paper, liquid crystal compound Cholest-5-en-3-ol(3β)-4-(2-propenyloxy)benzoate was synthesised, and a liquid crystal surface (LC surface) is prepared by heating the liquid crystal compound to 250°C and then cooling it. We determined ice-phobic properties of LC surface using differential scanning calorimetry (DSC) and polarised optical microscope (POM). A phenomenon that the freezing of water droplet on the LC surface is delayed was found. Compared with the two measurement methods, we obtained similar result that water freezing temperature was delayed nearly by 8°C on average on the LC surface. A process of ice/frost formation is observed using POM. The results displayed that the glass wafer without LC was covered completely by ice/frost, whereas on the LC surface at the same temperature no ice/frost was formed. Characteristics of LC surface were observed by field emission scanning electron microscope (FESEM) and Fourier transform infrared (FT-IR) imaging system. We suggest that the reason behind anti-ice surface is related to surface molecules and this is an important factor which may have an effect on anti-icing property. Graphical Abstract: